Future Internet - FIS 2009 Second Future Internet Symposium, FIS 2009, Berlin, Germany, September 1-3, 2009 - Zseby, Tanja.; Savola, Reijo.; Pistore, Marco. (Lecture Notes in Computer Science,, 2010)
This book constitutes the proceedings of the Second Future Internet Symposium, held in Berlin, Germany in September 2009. The ten papers accepted for presentation were carefully reviewed and selected from many submissions. The included papers propose novel ideas and results related to the Future Internet infrastructure and its virtualization, the Internet of services and of things, the problem of accessing the resources available on the Future Internet, the applications that will be available in the Future Internet.